UPDATE KNOWLEDGE: PERAN GENDER DAN MASA KERJA TERHADAP MOTIVASI KERJA PERAWAT DI RAWAT INAP RUMAH SAKIT - Rejeki, Mirah; Rizky, Wahyu; Putri, Sely Aprianda Syah; Oktavia, Fania; Oktaviani, Afifah Nurwidad; Valentina, Amara; Putri, Tika Kusuma; Ayu, Ajeng Karisma; Ferianti, Amalia Diah (Jurnal Pengabdian Masyarakat (Jupemas), 2024)
Quantitative workload can be expressed as the amount of work required to fulfil a patient's medical needs. High-quality workload represents a high level of responsibility in patient care. Nurses' workload is the most important predictor of mental health, stress, job dissatisfaction, fatigue, and the presence of burnout. This service activity aims to provide and increase student knowledge about the Effect of Gender and Years of Service on Work Motivation of Nurses in Hospital Inpatients to Students of the Hospital Administration Study Program, Undergraduate Program, Faculty of Health Sciences, Kusuma Husada University, Surakarta by using a pre-experiment design with a research design of one group pretest and post-test design with a total of 35 students and the activity time in May 2024. This service uses quantitative research with multiple linear regression. There is an increase in the knowledge of participants before and after the provision of material marked by the pre-test and post test which shows that the level of knowledge before being given the material is 69% but after being given the material has increased to 89%. There is a significant difference between students' knowledge about gender roles and tenure on nurses' work motivation in hospital inpatient care.Keywords: Workload, Gender, Work motivation, Nurses, Hospitalisation